Aerobic and Resistance Exercise Improves Shoulder Function in Women Who Are Overweight or Obese and Have Breast Cancer: A Randomized Controlled Trial. Issue 10 (16th July 2019) - Sweeney, Frank C; Demark-Wahnefried, Wendy; Courneya, Kerry S; Sami, Nathalie; Lee, Kyuwan; Tripathy, Debu; Yamada, Kimiko; Buchanan, Thomas A; Spicer, Darcy V; Bernstein, Leslie; Mortimer, Joanne E; Dieli-Conwright, Christina M
Abtract: Background: Adverse upper limb musculoskeletal effects occur after surgical procedures and radiotherapy for breast cancer and can interfere with activities of daily living. Objective: The objective of this study was to examine the effects of a 16-week exercise intervention on shoulder function in women who are overweight or obese and have breast cancer. Design: This study was a randomized controlled trial. Setting: The study was performed at the Division of Biokinesiology and Physical Therapy at the University of Southern California. Participants: One hundred women with breast cancer were randomly allocated to exercise or usual-care groups. The mean (SD) age of the women was 53.5 (10.4) years, 55% were Hispanic white, and their mean (SD) body mass index was 33.5 (5.5) kg/m 2 . Intervention: The 16-week exercise intervention consisted of supervised, progressive, moderate to vigorous aerobic and resistance exercise 3 times per week. Measurements: Shoulder active range of motion, isometric muscular strength, and patient-reported outcome measures (including Disabilities of the Arm, Shoulder, and Hand and the Penn Shoulder Scale) were assessed at baseline, after the intervention, and at the 3-month follow-up (exercise group only). Differences in mean changes for outcomes were evaluated using mixed-model repeated-measures analysis. Results: Compared with the usual-care group, the exercise group experienced significant increases in shoulder active range of motion (the mean between-group differences and 95% confidence intervals (CIs) were as follows: shoulder flexion = 36.6° [95% CI = 55.2–20.7°], external rotation at 0° = 23.4° [95% CI = 31.1–12.5°], and external rotation at 90° = 34.3° [95% CI = 45.9–26.2°]), improved upper extremity isometric strength, and improved Disabilities of the Arm, Shoulder, and Hand and Penn Shoulder Scale scores. Limitations: Limitations include a lack of masking of assessors after the intervention, an attention control group, and statistical robustness (shoulder function was a secondary end point). Conclusions: A 16-week exercise intervention effectively improved shoulder function following breast cancer treatment in women who were overweight or obese, who were ethnically diverse, and who had breast cancer.